Organic-inorganic hybrid solid electrolyte membrane based on siO2 aerogel and preparation method
By combining highly dispersed silica aerogel with flame-retardant polyethyleneimine, a SiO2 aerogel organic-inorganic hybrid solid electrolyte membrane was prepared, solving the compatibility and structural control problems of silica aerogel in solid electrolytes and realizing a high-performance electrolyte membrane.
Patent Information
- Application Number
- CN202511841567.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2045-12-09
AI Technical Summary
In existing technologies, the use of silica aerogels in solid electrolytes suffers from poor compatibility, interface defects, and ion transport blockage. Furthermore, traditional preparation methods make it difficult to precisely control the aerogel structure, affecting the uniformity and mechanical integrity of the electrolyte membrane.
A combination of highly dispersed silica aerogel, lithium salt, flame-retardant polyethyleneimine, and polyethylene oxide was used to prepare SiO2 aerogel via a co-precursor method, constructing an organic-inorganic hybrid solid electrolyte membrane. The reaction of N-imidazolium propyltrimethoxysilane and flame-retardant polyethyleneimine was utilized to generate imidazolium bromide and phosphorus-functionalized ionic liquid structures, thereby improving dispersibility and ionic conductivity.
It achieves high ionic conductivity, excellent thermal stability, flame retardancy and electrochemical stability, significantly improving the overall performance of the electrolyte membrane.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, specifically to an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel and its preparation method. Background Technology
[0002] With the rapid development of new energy vehicles, portable electronic devices, and large-scale energy storage systems, the demand for high-energy-density and high-safety lithium-ion batteries is becoming increasingly urgent. While traditional lithium-ion battery electrolytes possess high ionic conductivity, they also pose safety hazards such as flammability, leakage, and poor thermal stability, severely limiting battery safety performance and lifespan. Therefore, developing solid-state electrolytes that combine high ionic conductivity, excellent thermal stability, and a wide electrochemical window has become an important research direction for overcoming the limitations of lithium-ion battery electrolytes.
[0003] Solid electrolytes mainly fall into three categories: inorganic ceramic electrolytes, polymer electrolytes, and organic-inorganic hybrid electrolytes. Among them, inorganic ceramic electrolytes such as LLZO and LATP possess high ionic conductivity and good thermal stability, but they are rigid, have poor interfacial contact, and are difficult to process. Polymer electrolytes such as PEO-based electrolytes offer good flexibility, are easy to form films, and have good interfacial compatibility, but their room-temperature ionic conductivity is relatively low, and their thermal and electrochemical stability are limited, and they are flammable. To combine the advantages of both, organic-inorganic hybrid solid electrolytes have received widespread attention in recent years. By introducing functional inorganic fillers into the polymer matrix, not only can mechanical strength and thermal stability be improved, but lithium salt dissociation can also be promoted, and continuous ion transport channels can be constructed, thereby effectively improving ionic conductivity and electrochemical stability.
[0004] Silica aerogel, as a lightweight material with a three-dimensional nanoporous network structure, can reach a thickness of up to 1000m. 2 With its ultra-high specific surface area (above 1 / g), low density, excellent thermal insulation, and chemical inertness, silica aerogel shows great potential in the field of energy materials. Introducing it as an inorganic framework into polymer electrolyte systems can form interpenetrating or semi-interpenetrating network structures. On the one hand, its abundant surface functional groups (such as -OH) interact with lithium salts or polymer segments, enhancing lithium-ion migration capabilities. On the other hand, its highly interconnected nanopores can serve as "highways" for rapid ion transport, while simultaneously inhibiting polymer crystallization, increasing the proportion of amorphous regions, and further optimizing ion conduction performance. Furthermore, silica aerogel itself can withstand temperatures above 500 °C, exhibiting excellent thermal stability and electrochemical inertness, which helps improve the overall safety and operating voltage window of the composite electrolyte.
[0005] However, the use of silica aerogels in solid electrolytes still faces many challenges in the current technology: for example, the aerogel has poor compatibility with the polymer matrix, which can easily lead to interface defects and ion transport blockage; another example is that the structure of aerogels prepared by the traditional sol-gel method is difficult to control precisely, which affects the uniformity and mechanical integrity of the electrolyte membrane; and yet another challenge is that while maintaining the porous structure of the aerogel, it is impossible to achieve high lithium salt loading and efficient ion conduction.
[0006] Therefore, there is an urgent need to develop organic-inorganic hybrid solid electrolyte membranes based on SiO2 aerogel and their preparation methods to improve ionic conductivity, thermal stability and electrochemical stability, and provide key material support for high-safety and high-performance all-solid-state lithium batteries. Summary of the Invention
[0007] The purpose of this invention is to provide an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel and its preparation method, so as to solve the technical problems mentioned in the background art.
[0008] The technical solution to achieve the objective of this invention is:
[0009] In a first aspect, the present invention provides an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel. The raw material components mainly include highly dispersed silica aerogel, lithium salt, polyethylene oxide, and flame-retardant polyethyleneimine. The highly dispersed silica aerogel and flame-retardant polyethyleneimine are first mixed and reacted, then lithium salt is added and the reaction is continued by stirring. Finally, polyethylene oxide and lithium-ion conductor are added and mixed to obtain a slurry. The slurry is then used to form a membrane.
[0010] Furthermore, the highly dispersed silica aerogel is prepared using a co-precursor method with N-imidazolium propyltrimethoxysilane and tetraethyl orthosilicate as silicon sources.
[0011] Furthermore, the lithium salt comprises at least lithium bis(trifluoromethanesulfonyl)imide.
[0012] Furthermore, the flame-retardant polyethyleneimine is obtained by reacting diethyl phosphite with polyethyleneimine and then reacting it with 1,3-dibromopropane.
[0013] In a second aspect, the present invention replaces the preparation method of the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel as described in the first aspect, and the preparation steps are as follows:
[0014] (1) Add highly dispersed silica aerogel and flame-retardant polyethyleneimine to toluene, stir and disperse evenly, then heat and reflux for 23-24 hours. After the reaction, filter, wash and dry to obtain the first mixture.
[0015] (2) After stirring and dispersing the initial mixture, lithium bis(trifluoromethanesulfonylimide), deionized water and dichloromethane evenly, continue the reaction for 5-7 hours. After the reaction is completed, filter, wash and dry to obtain mixture A.
[0016] (3) Mix A, second lithium salt and acetonitrile are stirred and dispersed evenly, then sonicated for 10-20 min, then polyethylene oxide is added while stirring, and stirring is continued for 11-13 h, followed by sonication for 80-100 min, then placed in a refrigerator for 5-15 min, and vacuum degassing for 20-40 min to obtain slurry. The slurry is then used to form a membrane to obtain an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel.
[0017] Further, the mass ratio of the highly dispersed silica aerogel, polyethylene oxide, flame-retardant polyethyleneimine, lithium bis(trifluoromethanesulfonylimide), and the second lithium salt is (0.5~0.6):(4~4.2):1:(0.41~0.49):(1.4~1.6); the second lithium salt includes one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB.
[0018] Further, the mass ratio of the highly dispersed silica aerogel to toluene is (0.5~0.6):(1.8~2.0); the mass ratio of lithium bis(trifluoromethanesulfonylimide), deionized water, and dichloromethane is (0.41~0.49):(0.99~1.19):(1.98~2.36); and the mass ratio of acetonitrile to flame-retardant polyethyleneimine is (0.5~0.6):1.
[0019] Further, the preparation steps of the highly dispersed silica aerogel are as follows: N-imidazolium propyltrimethoxysilane is sequentially mixed with anhydrous ethanol and deionized water, and stirred continuously for 11-13 h. Then, tetraethyl orthosilicate is added and stirred for another 8-12 min. The gel is allowed to stand at -20 to -15 °C, and then aged in anhydrous ethanol at 25-60 °C for 23-25 h. Finally, supercritical drying is performed to obtain the highly dispersed silica aerogel. The volume ratio of N-imidazolium propyltrimethoxysilane, anhydrous ethanol, deionized water, and tetraethyl orthosilicate is (1-5):(10-20):(0.9-2.7):5.
[0020] Further, the preparation steps of the flame-retardant polyethyleneimine are as follows: branched polyethyleneimine and triethylamine are dispersed in dichloromethane, diethyl phosphite and carbon tetrachloride are added under ice bath conditions, the mixture is heated to room temperature and reacted for 11-13 hours, then the solvents dichloromethane and carbon tetrachloride are evaporated to remove them, and then dried to obtain pre-modified polyethyleneimine; the pre-modified polyethyleneimine is added to 1,3-dibromopropane and mixed, and refluxed under nitrogen protection for 3-5 hours, and then excess 1,3-dibromopropane is removed by vacuum distillation to obtain flame-retardant polyethyleneimine.
[0021] Further, the mass ratio of the branched polyethyleneimine, diethyl phosphite, triethylamine, dichloromethane, and tetrachloromethane is 1:(4~6):(4.8~7.2):(6~9):(4.8~7.2); the mass ratio of the pre-modified polyethyleneimine to 1,3-dibromopropane is 1:(6~8).
[0022] By adopting the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The present invention obtains an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel by using a slurry in which the raw material components mainly include highly dispersed silica aerogel, lithium salt, polyethylene oxide and flame-retardant polyethyleneimine. The resulting membrane has high ionic conductivity, excellent thermal stability, flame retardancy and electrochemical stability.
[0024] (2) The highly dispersed silica aerogel of the present invention is prepared by a co-precursor method using N-imidazolium propyltrimethoxysilane and tetraethyl orthosilicate as silicon sources. Tetraethyl orthosilicate, as a traditional inorganic silicon source, constructs the basic three-dimensional network framework of silica aerogel, giving the material high specific surface area, high porosity and excellent thermal stability. N-imidazolium propyltrimethoxysilane, as an organic-inorganic hybrid silane precursor, has imidazolium rings in its molecules that not only participate in network construction during gelation but are also firmly anchored to the surface of the aerogel framework. On the one hand, the steric hindrance effect of organic groups effectively inhibits the aggregation of highly dispersed silica aerogel and significantly improves the dispersibility of aerogel powder in polyethylene oxide and flame-retardant polyethyleneimine polymer matrices. On the other hand, the organic-inorganic hybrid network structure formed by the co-precursor method itself has higher chemical and mechanical stability, which helps to maintain the structural integrity of the electrolyte membrane under long-term electrochemical cycling and high-temperature environment.
[0025] (3) The flame-retardant polyethyleneimine of the present invention is obtained by reacting ethyl phosphite with polyethyleneimine and then reacting it with 1,3-dibromopropane. First, the active PH bond in diethyl phosphite undergoes an addition reaction with the amino group on the polyethyleneimine (PEI) molecular chain, covalently grafting the phosphorus-containing group onto the PEI backbone. Subsequently, the remaining ethoxy group in diethyl phosphite undergoes a nucleophilic substitution reaction with the bromine atom in 1,3-dibromopropane, further attaching the bromopropyl group to the phosphorus atom, thereby enhancing the flame retardant effect of the PEI backbone. The side chains of organophosphonates containing -P(O)(OEt)(CH2CH2CH2Br) structural units were constructed, which not only introduced bromine, which has a highly efficient gas-phase flame retardant effect, but also retained the ability of phosphorus to promote char formation and form a heat-insulating and oxygen-barrier protective layer in the condensed phase. At the same time, the nitrogen element rich in PEI itself can release non-combustible gases such as ammonia and nitrogen during pyrolysis, diluting the concentration of combustible volatiles. Under the synergistic effect of phosphorus, nitrogen and bromine, the intrinsic flame retardant properties of flame-retardant polyethyleneimine are significantly improved.
[0026] (4) The flame-retardant polyethyleneimine of the present invention is prepared by branched polyethyleneimine. The polar amino and phosphonate groups in the branched flame-retardant polyethyleneimine can form multiple hydrogen bonds and coordination with PEO segments, highly dispersed silica aerogel and lithium salt, effectively stabilizing the polymer matrix structure, inhibiting the increase of PEO crystallinity and excessive chain movement at high temperature, and significantly enhancing the thermal stability of the film. At the same time, it also helps to passivate the electrode / electrolyte interface, reduce the occurrence of side reactions, broaden the electrochemical window, and improve the electrochemical stability during cycling.
[0027] (5) In the preparation of the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel, the highly dispersed silica aerogel is first mixed and reacted with flame-retardant polyethyleneimine, then lithium salt is added and the reaction is continued by stirring. Finally, polyethylene oxide and lithium-ion conductor are added and mixed to obtain the final product. Specifically: First, the highly dispersed silica aerogel is mixed and reacted with flame-retardant polyethyleneimine. The imidazole group introduced by N-imidazolium propyltrimethoxysilane on the surface of the aerogel undergoes a nucleophilic substitution reaction with the bromopropane structure on the side chain of flame-retardant polyethyleneimine to generate imidazole bromide in situ. Then, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is added so that the bromide ions are absorbed by the TFSI. - Anion substitution forms imidazole cations and TFSI. -A phosphorus-functionalized ionic liquid structure composed of anions was constructed. Anchoring this ionic liquid structure to the surface of silica aerogel via covalent bonds significantly improved the dispersion stability of the aerogel in the polymer matrix, preventing aggregation, and also created interfacial microregions with excellent ionic conductivity. Simultaneously, the phosphonate functional groups introduced onto the imidazole ring effectively suppressed the deprotonation tendency of the imidazole cation at low potentials, thereby significantly enhancing its electrochemical stability within the battery operating voltage window and preventing the reductive decomposition of the imidazole ring. Furthermore, the phosphine oxide group in the phosphonate structure contains lone pairs of electrons, exhibiting strong coordination ability for lithium ions. This effectively weakens the Coulombic interaction between lithium ions and bis(trifluoromethanesulfonyl)imide anions, promoting lithium salt dissociation and locally forming Li-containing compounds. + -P=O coordination and Li + -TFSI - The dynamic transport environment is characterized by weak binding. In the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel, not only is the continuous ion pathway provided by the three-dimensional nanopores of the aerogel retained, but also a highly efficient "dual lithium-ion transport channel" is constructed through phosphorus-functionalized ionic liquid interface. That is, the chain segment motion conduction in the polymer matrix and the rapid jumping conduction mechanism of the inorganic / ionic liquid interface are used at the same time to significantly improve the overall ionic conductivity. The resulting electrolyte membrane achieves high ionic conductivity while also having excellent thermal stability, flame retardancy and electrochemical stability. Detailed Implementation
[0028] To better understand the above technical solution, the following will provide a detailed explanation of the technical solution in conjunction with specific implementation methods.
[0029] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.
[0030] The following embodiments are only used to illustrate the technical solutions of the present invention more clearly, and should not be used to limit the scope of protection of the present invention.
[0031] Branched polyethyleneimine was purchased from Chengdu Xiya Reagent Co., Ltd., with Mw=800g / mol and PDI=1.3.
[0032] The second lithium salt is LiClO4.
[0033] Example
[0034] The preparation method of organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel includes the following steps:
[0035] (1) Add 0.5~0.6 parts by weight of highly dispersed silica aerogel and 1 part by weight of flame-retardant polyethyleneimine to 1.8~2.0 parts by weight of toluene, stir and disperse evenly, then heat and reflux for 23~24h. After the reaction, filter, wash and dry to obtain the first mixture.
[0036] (2) After stirring and dispersing the first mixture, 0.41~0.49 parts by weight of lithium bis(trifluoromethanesulfonylimide), 0.99~1.19 parts by weight of deionized water, and 1.98~2.36 parts by weight of dichloromethane evenly, continue to react for 5~7 hours. After the reaction is completed, filter, wash, and dry to obtain mixture A.
[0037] (3) Mix A, 1.4~1.6 parts by mass of second lithium salt and 0.5~0.6 parts by mass of acetonitrile are stirred and dispersed evenly, then sonicated for 10~20 min, then 4~4.2 parts by mass of polyethylene oxide are added while stirring, and stirring is continued for 11~13 h, followed by sonication for 80~100 min, then placed in a refrigerator for 5~15 min, and vacuum degassing for 20~40 min to obtain slurry. The slurry is poured onto release paper and naturally extended for 15 min, then heated at 50℃ for 30 min, then heating is stopped, and the residual heat is used for 30 min, and then placed in a vacuum oven at 50℃ for 10 h to obtain an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel.
[0038] The preparation steps of highly dispersed silica aerogel are as follows: N-imidazolium propyltrimethoxysilane is successively mixed with anhydrous ethanol and deionized water, and stirred continuously for 11-13 h. Then, tetraethyl orthosilicate is added and stirred for another 8-12 min. The gel is allowed to stand at -20 to -15 °C, and then aged in anhydrous ethanol at 25-60 °C for 23-25 h. Finally, supercritical drying is performed to obtain highly dispersed silica aerogel. The volume ratio of N-imidazolium propyltrimethoxysilane, anhydrous ethanol, deionized water and tetraethyl orthosilicate is (1-5):(10-20):(0.9-2.7):5.
[0039] The preparation steps of flame-retardant polyethyleneimine are as follows: 1 part by mass of branched polyethyleneimine and 4.8-7.2 parts by mass of triethylamine are dispersed in 6-9 parts by mass of dichloromethane. Under ice bath conditions, 4-6 parts by mass of diethyl phosphite and 4.8-7.2 parts by mass of carbon tetrachloride are added. After heating to room temperature, the reaction is carried out for 11-13 hours. Then, the solvents dichloromethane and carbon tetrachloride are evaporated to remove the solvents, and then dried to obtain pre-modified polyethyleneimine. 1 part by mass of pre-modified polyethyleneimine is added to 6-8 parts by mass of 1,3-dibromopropane and mixed. The mixture is refluxed under nitrogen protection for 3-5 hours. Then, excess 1,3-dibromopropane is removed by vacuum distillation to obtain flame-retardant polyethyleneimine.
[0040] Example 1
[0041] The preparation method of organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel includes the following steps:
[0042] (1) 0.5 parts by mass of highly dispersed silica aerogel and 1 part by mass of flame-retardant polyethyleneimine were added to 1.8 parts by mass of toluene, stirred and dispersed evenly, and then heated and refluxed for 23 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain the first mixture.
[0043] (2) After stirring and dispersing the first mixture, 0.41 parts by weight of lithium bis(trifluoromethanesulfonylimide), 0.99 parts by weight of deionized water, and 1.98 parts by weight of dichloromethane evenly, continue to react for 5 hours. After the reaction is completed, filter, wash, and dry to obtain mixture A.
[0044] (3) Mix A, 1.4 parts by mass of second lithium salt and 0.5 parts by mass of acetonitrile are stirred and dispersed evenly, then sonicated for 10 min, then 4 parts by mass of polyethylene oxide are added while stirring, and stirring is continued for 11 h and then sonicated for 80 min. Then, the mixture is placed in a refrigerator for 5 min and vacuum degassing for 20 min to obtain a slurry. The slurry is poured onto the release paper and naturally extended for 15 min. Then, it is heated at 50°C for 30 min and then the heating is stopped. The residual heat is used for heating for 30 min. Then, it is placed in a vacuum oven at 50°C for 10 h to obtain an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel with a thickness of 189 μm.
[0045] The preparation steps of highly dispersed silica aerogel are as follows: N-imidazolium propyltrimethoxysilane is successively mixed with anhydrous ethanol and deionized water, and stirred continuously for 11 h. Then, tetraethyl orthosilicate is added and stirred for another 8 min. The gel is allowed to stand at -20℃, and then aged in anhydrous ethanol at 25℃ for 25 h. Finally, supercritical drying is performed to obtain highly dispersed silica aerogel. The volume ratio of N-imidazolium propyltrimethoxysilane, anhydrous ethanol, deionized water and tetraethyl orthosilicate is 1:10:0.9:5.
[0046] The preparation steps of flame-retardant polyethyleneimine are as follows: 1 part by mass of branched polyethyleneimine and 4.8 parts by mass of triethylamine are dispersed in 6 parts by mass of dichloromethane. 4 parts by mass of diethyl phosphite and 4.8 parts by mass of carbon tetrachloride are added under ice bath conditions. The mixture is heated to room temperature and reacted for 11 hours. Then, the solvents dichloromethane and carbon tetrachloride are evaporated to remove the mixture, followed by drying to obtain pre-modified polyethyleneimine. 1 part by mass of pre-modified polyethyleneimine is added to 6 parts by mass of 1,3-dibromopropane and mixed. The mixture is refluxed under nitrogen protection for 3 hours. Then, excess 1,3-dibromopropane is removed by vacuum distillation to obtain flame-retardant polyethyleneimine.
[0047] Example 2
[0048] The preparation method of organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel includes the following steps:
[0049] (1) 0.55 parts by weight of highly dispersed silica aerogel and 1 part by weight of flame-retardant polyethyleneimine were added to 1.9 parts by weight of toluene, stirred and dispersed evenly, and then heated and refluxed for 24 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain the first mixture.
[0050] (2) The first mixture, 0.45 parts by weight of lithium bis(trifluoromethanesulfonylimide), 1.09 parts by weight of deionized water and 2.17 parts by weight of dichloromethane were stirred and dispersed evenly, and the reaction was continued for 6 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain mixture A.
[0051] (3) Mix A, 1.5 parts by mass of second lithium salt and 0.55 parts by mass of acetonitrile are stirred and dispersed evenly, then sonicated for 15 min, then 4.1 parts by mass of polyethylene oxide are added while stirring, and stirring is continued for 12 h, followed by sonication for 90 min, then placed in a refrigerator for 10 min, and vacuum degassing for 30 min to obtain slurry. The slurry is poured onto release paper and naturally extended for 15 min, then heated at 50℃ for 30 min, then heating is stopped, and the residual heat is used for 30 min, and then placed in a vacuum oven at 50℃ for 10 h to obtain an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel with a thickness of 207 μm.
[0052] The preparation steps of highly dispersed silica aerogel are as follows: N-imidazolium propyltrimethoxysilane is successively mixed with anhydrous ethanol and deionized water, and stirred continuously for 12 h. Then, tetraethyl orthosilicate is added and stirred for another 10 min. The gel is allowed to stand at -20℃, and then aged in anhydrous ethanol at 60℃ for 24 h. Finally, supercritical drying is performed to obtain highly dispersed silica aerogel. The volume ratio of N-imidazolium propyltrimethoxysilane, anhydrous ethanol, deionized water and tetraethyl orthosilicate is 3:15:1.8:5.
[0053] The preparation steps of flame-retardant polyethyleneimine are as follows: 1 part by mass of branched polyethyleneimine and 6 parts by mass of triethylamine are dispersed in 7.5 parts by mass of dichloromethane. 5 parts by mass of diethyl phosphite and 6 parts by mass of carbon tetrachloride are added under ice bath conditions. The mixture is heated to room temperature and reacted for 12 hours. Then, the solvents dichloromethane and carbon tetrachloride are evaporated to remove the mixture, followed by drying to obtain pre-modified polyethyleneimine. 1 part by mass of pre-modified polyethyleneimine is added to 7 parts by mass of 1,3-dibromopropane and mixed. The mixture is refluxed under nitrogen protection for 4 hours. Then, excess 1,3-dibromopropane is removed by vacuum distillation to obtain flame-retardant polyethyleneimine.
[0054] Example 3
[0055] The preparation method of organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel includes the following steps:
[0056] (1) 0.6 parts by weight of highly dispersed silica aerogel and 1 part by weight of flame-retardant polyethyleneimine were added to 2.0 parts by weight of toluene, stirred and dispersed evenly, and then heated and refluxed for 24 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain the first mixture.
[0057] (2) The first mixture, 0.49 parts by weight of lithium bis(trifluoromethanesulfonylimide), 1.19 parts by weight of deionized water and 2.36 parts by weight of dichloromethane were stirred and dispersed evenly, and the reaction was continued for 7 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain mixture A.
[0058] (3) Mixture A, 1.6 parts by mass of second lithium salt and 0.6 parts by mass of acetonitrile are stirred and dispersed evenly, then sonicated for 20 min, then 4.2 parts by mass of polyethylene oxide are added while stirring, and stirring is continued for 13 h, followed by sonication for 100 min, then placed in a refrigerator for 15 min, and vacuum degassing for 40 min to obtain slurry. The slurry is poured onto release paper and naturally extended for 15 min, then heated at 50℃ for 30 min, then heating is stopped, and the residual heat is used for 30 min, and then placed in a vacuum oven at 50℃ for 10 h to obtain an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel with a thickness of 196 μm.
[0059] The preparation steps of highly dispersed silica aerogel are as follows: N-imidazolium propyltrimethoxysilane is successively mixed with anhydrous ethanol and deionized water, and stirred continuously for 13 h. Then, tetraethyl orthosilicate is added and stirred for another 12 min. The gel is allowed to stand at -15℃, and then aged in anhydrous ethanol at 60℃ for 23 h. Finally, supercritical drying is performed to obtain highly dispersed silica aerogel. The volume ratio of N-imidazolium propyltrimethoxysilane, anhydrous ethanol, deionized water and tetraethyl orthosilicate is 5:20:2.7:5.
[0060] The preparation steps of flame-retardant polyethyleneimine are as follows: 1 part by mass of branched polyethyleneimine and 7.2 parts by mass of triethylamine are dispersed in 9 parts by mass of dichloromethane. 6 parts by mass of diethyl phosphite and 7.2 parts by mass of carbon tetrachloride are added under ice bath conditions. The mixture is heated to room temperature and reacted for 13 hours. Then, the solvents dichloromethane and carbon tetrachloride are evaporated to remove the solvents, and the mixture is dried to obtain pre-modified polyethyleneimine. 1 part by mass of pre-modified polyethyleneimine is added to 8 parts by mass of 1,3-dibromopropane and mixed. The mixture is refluxed under nitrogen protection for 5 hours. Then, excess 1,3-dibromopropane is removed by vacuum distillation to obtain flame-retardant polyethyleneimine.
[0061] Comparative Example 1
[0062] The difference between Comparative Example 1 and Example 2 lies in the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel. The main raw material components include silica aerogel, lithium salt, polyethylene oxide, and flame-retardant polyethyleneimine. The remaining components and steps are the same as in Example 2.
[0063] Comparative Example 2
[0064] The difference between Comparative Example 2 and Example 2 lies in the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel. The raw material components mainly include highly dispersed silica aerogel, lithium salt, polyethylene oxide, and polyethyleneimine. The remaining components and steps are the same as in Example 2.
[0065] Comparative Example 3
[0066] The difference between Comparative Example 3 and Example 2 is that the raw material components of the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel mainly include silica aerogel, lithium salt, polyethylene oxide, and polyethyleneimine, while the remaining components and steps are the same as in Example 2.
[0067] Comparative Example 4
[0068] The difference between Comparative Example 4 and Example 2 lies in the preparation steps of the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel, which include: stirring and dispersing 0.55 parts by mass of highly dispersed silica aerogel, 1 part by mass of flame-retardant polyethyleneimine, 0.45 parts by mass of lithium bis(trifluoromethanesulfonylimide), 1.5 parts by mass of the second lithium salt, and 0.55 parts by mass of acetonitrile until uniform, then sonicating for 15 minutes, then adding 4.1 parts by mass of polyethylene oxide while stirring, continuing to stir for 12 hours, then sonicating for 90 minutes, then freezing in a refrigerator for 10 minutes, and then vacuum degassing for 30 minutes to obtain a slurry. The slurry is poured onto release paper and allowed to spread naturally for 15 minutes, then heated at 50°C for 30 minutes, then heating is stopped, and the residual heat is used for heating for 30 minutes. Finally, it is placed in a vacuum oven at 50°C for 10 hours to obtain the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel. The remaining components and steps are the same as in Example 2.
[0069] Example of effect
[0070] The organic-inorganic hybrid solid electrolyte membranes prepared in Examples 1-3 and Comparative Examples 1-4 were used to assemble blocked batteries in the form of stainless steel SS / organic-inorganic hybrid solid electrolyte membrane / stainless steel SS to determine the ionic conductivity of the polymer solid electrolyte. Half-cells in the form of lithium Li / organic-inorganic hybrid solid electrolyte membrane / stainless steel SS were assembled to determine the electrochemical window of the polymer solid electrolyte's electrochemical stability. Before use, the stainless steel sheets were ultrasonically cleaned in acetone for at least 12 hours and then dried in a 60°C oven. Except for the blocked batteries, which could be assembled directly in atmospheric conditions, all other assembly operations had to be completed in a glove box using a button cell packaging machine at 50 kg / cm². 2 The battery is then sealed under pressure. After sealing, the battery is placed in a 60°C oven and left to stand for 12 hours to allow the electrolyte membrane to fully contact the electrode plates, in preparation for testing.
[0071] Table 1 below shows the performance test results of the organic-inorganic hybrid solid electrolyte membranes prepared in Examples 1-3 and Comparative Examples 1-4:
[0072] Table 1
[0073]
[0074] Table 1 shows that the organic-inorganic hybrid solid electrolyte membranes prepared in Examples 1-3 and Comparative Examples 1-4 possess high ionic conductivity, flame retardancy, and electrochemical stability.
[0075] The difference between Comparative Example 1 and Example 2 is that the silica aerogel was prepared by sol-gel method using tetraethyl orthosilicate as the silicon source, rather than by co-precursor method using N-imidazolium propyltrimethoxysilane and tetraethyl orthosilicate as silicon sources. The silica aerogel exhibited agglomeration, and the resulting organic-inorganic hybrid solid electrolyte membrane had lower ionic conductivity and weaker flame retardancy and electrochemical stability.
[0076] The difference between Comparative Example 2 and Example 2 lies in the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel, where the raw material component is polyethyleneimine instead of flame-retardant polyethyleneimine. The resulting organic-inorganic hybrid solid electrolyte membrane has lower ionic conductivity, weaker flame retardancy, and weaker electrochemical stability.
[0077] The difference between Comparative Example 3 and Example 2 is that the raw material components of the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel are silica aerogel and polyethyleneimine, instead of flame-retardant polyethyleneimine and highly dispersed silica aerogel. The resulting organic-inorganic hybrid solid electrolyte membrane has lower ionic conductivity, weaker flame retardancy and electrochemical stability.
[0078] The difference between Comparative Example 4 and Example 2 is that the organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel is prepared by directly mixing highly dispersed silica aerogel, flame-retardant polyethyleneimine, lithium bis(trifluoromethanesulfonylimide), second lithium salt, acetonitrile, and polyethylene oxide. The resulting organic-inorganic hybrid solid electrolyte membrane has lower ionic conductivity and weaker electrochemical stability.
[0079] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An organic-inorganic hybrid solid electrolyte membrane based on Si02 aerogel, characterized in that, The raw material components include high-dispersion silica aerogel, lithium salt, polyethylene oxide, and flame-retardant polyethylene imine; the high-dispersion silica aerogel and the flame-retardant polyethylene imine are mixed and reacted first, then the first lithium salt is added and the reaction is continued, finally the polyethylene oxide and the second lithium salt are added and mixed to obtain a slurry, and the slurry is prepared into a film; the high-dispersion silica aerogel is prepared by using N-imidazole propyl trimethoxysilane and tetraethyl orthosilicate as the silicon source by a co-precursor method; the first lithium salt at least includes lithium bis(trifluoromethanesulfonyl)imide; the flame-retardant polyethylene imine is obtained by reacting diethyl phosphite with polyethylene imine and then reacting with 1,3-dibromopropane.
2. The method for preparing a SiO2 aerogel-based organic-inorganic hybrid solid electrolyte membrane according to claim 1, characterized in that, The preparation steps are as follows: (1) the high-dispersion silica aerogel and the flame-retardant polyethylene imine are added into toluene and stirred and dispersed uniformly, then heated and refluxed for 23-24 h, after the reaction is completed, filtered, washed, and dried to obtain the first mixed material; (2) the first mixed material, lithium bis(trifluoromethanesulfonyl)imide, deionized water, and dichloromethane are stirred and dispersed uniformly, then the reaction is continued for 5-7 h, after the reaction is completed, filtered, washed, and dried to obtain mixed material A; (3) mixed material A, the second lithium salt, and acetonitrile are stirred and dispersed uniformly, then ultrasonic treated for 10-20 min, then the polyethylene oxide is added while stirring, the stirring is continued for 11-13 h, then ultrasonic treated for 80-100 min, then placed in a refrigerator and refrigerated for 5-15 min, then vacuum degassed for 20-40 min to obtain a slurry, and the slurry is prepared into a film to obtain an organic-inorganic hybrid solid-state electrolyte film based on SiO2 aerogel.
3. The method for preparing a SiO2 aerogel-based organic-inorganic hybrid solid-state electrolyte membrane according to claim 2, characterized in that, The mass ratio of the high-dispersion silica aerogel, polyethylene oxide, flame-retardant polyethylene imine, lithium bis(trifluoromethanesulfonyl)imide, and the second lithium salt is (0.5-0.6):(4-4.2):1:(0.41-0.49):(1.4-1.6); the second lithium salt includes one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB.
4. The method for preparing an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel according to claim 2, characterized in that, The mass ratio of the high-dispersion silica aerogel and toluene is (0.5-0.6):(1.8-2.0); the mass ratio of lithium bis(trifluoromethanesulfonyl)imide, deionized water, and dichloromethane is (0.41-0.49):(0.99-1.19):(1.98-2.36); the mass ratio of acetonitrile and flame-retardant polyethylene imine is (0.5-0.6):
1.
5. The method for preparing an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel according to claim 2, characterized in that, The preparation steps of the high-dispersion silica aerogel are as follows: N-imidazole propyl trimethoxysilane is sequentially added into anhydrous ethanol and deionized water, continuously stirred for 11-13 h, then tetraethyl orthosilicate is added and stirred for 8-12 min, then gelled at-20--15℃, then aged in 25-60℃ anhydrous ethanol for 23-25 h, and finally supercritically dried to obtain the high-dispersion silica aerogel; wherein the volume ratio of N-imidazole propyl trimethoxysilane, anhydrous ethanol, deionized water, and tetraethyl orthosilicate is (1-5):(10-20):(0.9-2.7):
5.
6. The method for preparing an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel according to claim 2, characterized in that, The preparation steps of the flame-retardant polyethylene imine are as follows: branched polyethylene imine, triethylamine are dispersed in dichloromethane, diethyl phosphite and carbon tetrachloride are added under ice bath condition, the reaction is carried out for 11-13 hours after being warmed to room temperature, then the solvent dichloromethane and carbon tetrachloride are evaporated and removed, then drying is carried out, to obtain pre-modified polyethylene imine; the pre-modified polyethylene imine is mixed with 1,3-dibromopropane, and the reaction is carried out under reflux for 3-5 hours under nitrogen protection, then excess 1,3-dibromopropane is removed by distillation under reduced pressure, to obtain the flame-retardant polyethylene imine.
7. The method for preparing an organic-inorganic hybrid solid electrolyte membrane based on SiO2 aerogel according to claim 6, characterized in that, The mass ratio of the branched polyethylene imine, diethyl phosphite, triethylamine, dichloromethane, carbon tetrachloride is 1:(4-6):(4.8-7.2):(6-9):(4.8-7.2); the mass ratio of the pre-modified polyethylene imine and 1,3-dibromopropane is 1:(6-8).
Citation Information
Patent Citations
Composite solid electrolyte, preparation method thereof and solid-state battery
CN112002940A
Preparation method of composite solid electrolyte membrane
CN119361800A